The 48 Laws of Power - Greene, Robert (London Profile Books, 2002)
Drawn from 3,000 years of the history of power, this guide helps readers achieve for themselves what Queen Elizabeth I, Henry Kissinger, Louis XIV and Machiavelli learnt the hard way.
Keywords: Control -- Manipulative behavior -- Success